Safety evaluation and injury mechanism identification in launch abort system using finite element method - Akihiro UEDA; Shunsuke IMAIZUMI; Kodai NAKAGAWA; Keiichiro FUJIMOTO; Asuka HATANO; Satoshi IZUMI; Shinsuke SAKAI (Nihon Kikai Gakkai ronbunshu, 2018)
It has been long since the technology for human space flight system was established. In order to realize challenging manned space missions, further improvements in the system reliability and crew safety are essential. Comprehensive design and operation considerations based on the quantitative crew safety analysis are key issues. Crew injury risk prediction method due to the transient dynamic load such as the excessive water landing speed, the explosion overpressure, and the off-nominal acceleration of the launch abort system (LAS) are developed and investigated in this study. In the early design stages, parametric injury risk analysis should be carried out. For this purpose, an anthropomorphic test device (ATD) model based on the multi-body dynamics is suitable to cover the wide range of conditions. In addition, an human finite element model is employed for more detailed crew injury risk analysis. Although there have been comprehensive research efforts in the automotive safety fields for many years, further research efforts are needed for the crew safety of human space flight since a wider range of the magnitude and the direction of the impact load should be considered. This paper deals with the human injuries evaluation using finite element model. The results are compared with those using Hybrid-III and safety margin is evaluated in view of NASA injury criteria to extract highly damaged body region in both models. The validity of brain injury criteria BrIC is investigated by using mechanical properties in brain and new risk curve for BrIC suitable for LAS environment is finally proposed.